Antibacterial activity of tamoxifen derivatives against methicillin-resistant Staphylococcus aureus - Molina Panadero, Irene; Falcón Torres, Javier; Hmadcha, Abdelkrim; Princiotto, Salvatore; Cutarella, Luigi; Mori, Mattia; Dallavalle, Sabrina; Christodoulou, Michael S.; Smani, Younes (Frontiers in Pharmacology, 2025)
The development of new antimicrobial therapeutic strategies requires urgent attention to prevent the tens of millions of deaths predicted to occur by 2050 as a result of multidrug-resistant (MDR) bacterial infections. This study aimed to discover new tamoxifen derivatives with antimicrobial potential, particularly targeting methicillin-resistant Staphylococcus aureus (MRSA). The minimum inhibitory concentration (MIC) of 22 tamoxifen derivatives was determined against S. aureus reference and MRSA strains using microdilution assays. The antibacterial effects of selected tamoxifen derivatives against MRSA (USA7 strain) were assessed through bacterial growth assays. Additionally, bacterial membrane permeability and molecular dynamics (MD) simulation assays were performed. The MIC of the tamoxifen derivatives against reference S. aureus and MRSA strains ranged from to 16 to >64 μg/mL. Bacterial growth assays demonstrated that tamoxifen derivatives 2, 5, and 6, the only compounds bearing the electron-donating hydroxyl group in the para position on both phenyl rings of the tamoxifen skeleton, dose-dependently reduced the growth of the USA7 strain. Moreover, treatment of MRSA with derivatives 2 and 5 resulted in a slight increase of membrane permeabilization. Extensive MD simulations on the interaction between 5 and 6 and the S. aureus membrane model suggest that the compounds do not act by destabilizing the membrane integrity. These findings suggest that tamoxifen derivatives exhibit antibacterial activity against MRSA, potentially broadening the spectrum of available drug treatments for combating antimicrobial-resistant S. aureus.